Национальное государство в информационном обществе - Буць, Д. Є. (ХНУРЕ, 2021)
The article examines modern problems of the functioning and development of national states in the context of globalization and regionalization of the modern world. It is argued that the classical European nation state faced internal and external challenges caused by the processes of globalization and regionalization of the modern world. These challenges include social differentiation of the population, erosion of national identity, split in society, and many other problems. At the same time, the problem of state solvency is aggravated, more and more unrecognized or failed states appear, the transfer of state powers to other states or supranational entities
Keywords: философия; национальное государство